KEDUDUKAN KWITANSI SEBAGAI ALAT BUKTI DALAM JUAL BELI TANAH DI PENGADILAN NEGERI RENGAT KELAS II - Irza Legista; Emilda Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Even though national land law adopts the system of customary law, it has been regulated strictly and real in Article 37 paragraph (1) The Government Regulation Number 24 Year of 1997 about Land Registration, that buy and sell on land object must be conducted in front of authorized officer in this case is Land Titles Registrar (PPAT) and Article 2 Paragraph (1) Government Regulation Number 37 Year of 1998 about Position Regulation of Land Title Registrar (PPAT). In the state court Class II of Rengat are there some civil disputes in which the plaintiff and defendant did buy and sell land with invoice as the payment evidence and transfer of rights. The writing of this undergraduate thesis aims to find out the invoice position as the evidence in land buy and sell at State Court Class II of Rengat.The type of this research could be categorized into sociology research. This research was conducted at State Court Class II of Rengat, Indragiri Hulu Regency, while the population and samples were the parties related to the problem investigated in this research. Data collection was conducted by using interview method and library study. Data analysis was conducted by using qualitative data analysis and in taking conclusion the author used deductive method. The research result and discussion; the invoice as evidence of receiving money established by the parties can be used as written evidence based on Article 164 HIR/284 R.Bg. The invoice made is signed below by the parties as the written evidence (letter underhand) on land buy and sell as the initial evidence is not a strong enough. Therefore, the judge conducted material proving and place cheking on the dispute object. The author‟s suggesion; it is better that the evidence of land buy and sell is an authentic evidence in the form of Deed of Sale and Purchase (AJB) issued by PPAT because it has binding and perfect proof until the judge is binded to the truth proved by the deed. Keywords: Invoice Position-Evidence-Land Buy and Sell at State Court